The active roles of Rhodotorula mucilaginosa ZTHY2 in regulating antioxidant capacity and immune function of Leizhou black ducks - Wu, Jiang; Hu, Yingxin; Zhao, Namula; Yang, Wei; Chen, Zhibao (Frontiers in Veterinary Science, 2025)
Previous studies in mice have demonstrated that Rhodotorula mucilaginosa ZTHY2 can promote animal growth, enhance antioxidant and immune functions, and regulate intestinal flora in our laboratory. This study focuses on the Leizhou black duck, a local breed in Zhanjiang, to evaluate the effects of Rhodotorula mucilaginosa ZTHY2 on its growth, antioxidant capacity, and immune function. A total of 150 1-day-old male Leizhou black ducks, of similar size and healthy, were selected for this study and randomly assigned to five treatment groups. Each group contained three replicates with ten birds each. The control group (Control) was given a standard basal diet, while the RM group received a diet supplemented with ZTHY2 at concentrations of 2 × 107 (RM1), 2 × 108(RM2), or 2 × 109(RM3) CFU/kg, respectively. The LA group was supplemented with 2 × 109 CFU/kg of Lactobacillus acidophilus in addition to the basal diet. The feeding trial lasted 42 days. The analysis revealed significant improvements in the average body weight for the RM2 and RM3 groups, which were significantly higher than that of the control group (p < 0.05 and p < 0.01). Treatment with ZTHY2 induced a dose-dependent elevation in superoxide dismutase (SOD), catalase (CAT), glutathione peroxidase (GSH-Px), and SOD activities, and a reduction in malondialdehyde (MDA) content in the serum at 42 days. The serum levels of complement components C3 and C4, immunoglobulin IgG, and cytokines IFN-γ, IL-2, IL-4, IL-6, and TNF-α were significantly increased in Leizhou black ducks treated with ZTHY2 at 42-days post-treatment, with the therapeutic effect becoming more pronounced as the duration of the experiment prolonged. The greatest impact was observed at a dosage of 2 × 109 CFU/kg of ZTHY2. Moreover, ZTHY2 modulated the mRNA expression profiles of these cytokines in the thymus, spleen, and bursa, thereby sustaining the balance of immune dynamics. In summary, the supplementation of Rhodotorula mucilaginosa ZTHY2 at a dosage of 2 × 109 CFU/kg had been found to most effectively enhance the growth performance of Leizhou black ducks by optimizing their immune function and antioxidant capacity.